A laboratory study of the effect of varying beach slopes on bore-driven swash hydrodynamics - Deng, Bin; Zhang, Wen; Yao, Yu; Jiang, Changbo (Frontiers in Marine Science, 2022)
Swash-zone hydrodynamics have significant coastal geomorphological and engineering implications. However, there is still a research gap in fully understanding the response of bore-driven swash hydrodynamics to varying beach slopes. Therefore, in this study, laboratory experiments were performed in a flume to investigate the hydrodynamics of bore-driven swash flows over impermeable smooth beaches with a mild slope (1:35), a steep slope (1:10), and a composite slope (1:35-1:10), respectively. The designed swash events are produced by a collapse of dam-break generated bores. Wave gauges, ultrasonic displacement sensors, acoustic doppler velocimeter and the particle image velocimetry are used simultaneously to capture different phases (bore collapse, uprush and backwash) of bore evolution in the entire swash zone. The impacts of beach slope on the swash hydrodynamics in view of the shoreline movement, swash depth, and swash velocity are first analyzed. The formation and evolution of vortex structure on three beaches are also reported in this study.